EMPLOYEE PERFORMANCE OF PT. PLN (PERSERO) PALOPO AREA IN TERMS OF LEADERSHIP STYLE AND WORK DISCIPLINE - Salju Salju (Jurnal Ekonomi, 2022)
The purpose of this study was to examine the effect of leadership style and work discipline on employee performance at PT PLN (Persero) Palopo Area. This research uses quantitative methods with a research sample consisting of 34 respondents selected using the saturated sample formula. The independent variables in this study are leadership style and work discipline programs, while the dependent variable is employee performance. Multiple regression analysis techniques with the help of SPSS applications were used in this study. The results showed that partially, leadership style and work discipline programs have a positive and significant influence on employee performance. Simultaneously, the leadership style program and work discipline also have a positive and significant effect on employee performance. The adjusted R Square (R2) value obtained is 617 or 61.7%, meaning that 61.7% of the variation in employee performance can be explained by the leadership style program and work discipline. The remaining (100%- 61.7%= 38.3%) is explained by other factors included in the model.